Combining biochar production, electricity generation and district heating at Händelöverket district heating plant Assessing climate impact and economic viability through LCA and LCCA - Hakkarainen, Viktor; Bhalekar, Sayali (My University, 2020)
With recognition of the adverse effects of climate change, the IPCC has in a 2018 report put heavy emphasis on the need for carbon dioxide removal technologies to meet the global target of limiting global warming to 1.5 °C. There currently exists no one technology that can reverse the historical emissions of humanity, but instead there is a large spectrum of negative emission technologies. One of them is the process of turning biomass into a stable form of biochar through a pyrolyzing process, thereafter the biochar can be applied to agricultural fields to increase soil health and sequester the carbon in the soil. Pyrolyzing is the process of heating biomass in an anaerobic environment, dividing the biomass into three parts; biochar, bio-oil and synthetic gases. This thesis aims to determine the climate impact and the total cost of biochar production with subsequent soil application. Since large scale biochar production is in an early development phase, this is achieved by performing a life cycle assessment (LCA) as well as a life cycle costing assessment (LCCA). The chosen biochar production process was designed to pyrolyze wood residues (“GROT”) and combine the process with electricity and district heating production at the E.ON-owned district heating plant Händelöverket located in Norrköping, Sweden. This was to utilize the residual heat that is generated when pyrolyzing biochar and utilize the existing boiler “P13” as the combusting chamber for the process, circumventing the need to acquire a new combustion chamber. A cradle-to-grave LCA was performed with the software OpenLCA and the results showed that the sequestered carbon dioxide heavily outweighs the emissions that are generated to produce and apply the biochar. An alternative case was explored where a standalone combustion chamber was utilized to maximize the amount of operation hours. The results showed that the alternative case had a higher climate impact per functional unit, but a lower climate impact on a yearly basis. The costs for the LCCA in the alternative case were higher per functional unit but lower on a yearly basis. A cradle-to-gate LCCA was performed according to existing LCCA methodology found in literature. The costs and revenue were split up in a best-case and worst-case scenario. The two categories with the largest spread between the best- and worst case were: difference in revenue due to uncertainties of the biochar density and auxiliary installation costs such as piping, electronics etc. An NPV calculation was performed and showed a heavily positive NPV for the best-case scenario and a slightly negative NPV for the worst-case scenario. A sensitivity analysis was done for biochar carbon content, initial moisture of the feedstock, transport losses, feedstock price and discount rate. It was concluded that biochar is a viable path to achieve negative emissions from an environmental and cost perspective. The existence of a market for the produced biochar is vital for keeping biochar production economically viable, and market studies show that there exists a small-scale market today with large potential for expansion in 5-10 years. More cost-efficient options to sequester carbon dioxide exists, but with additional benefits of applying biochar to soil such as improved structure, porosity, water retention capacity and microbial properties gives biochar a competitive edge. Electricity generation and district heating production from the biochar process also gives additional benefits to using this method as a negative emission technology.
Keywords: Biochar; Pyrolysis; Negative Emission Technology; Life Cycle Assessment; Life Cycle Costing; Wood residue